‘SMART’ manufacturing method of oleochemical plants by determining fatty acid composition of C12 of palm kernel stearin using fuzzy logic system - Vitiyah Manimaran; Norliza Abd. Rahman; Jarinah Mohd Ali (Penerbit Universiti Kebangsaan Malaysia, 2020)
Industry 4.0 is the name given to the latest evolution in the digitalisation and automation of manufacturing processes. Transitioning to Industry 4.0 is an emerging imperative for chemical processing based manufacturers throughout the world. “Smart” equipments, products and factories are transforming how companies do business, both internally and with suppliers and customers. At the present moment palm oil products particularly, Palm Kernel Oil have become a major feedstock for the oleochemical industries in Malaysia. Since Malaysia accounts for 42% of the global production of palm oil products, it is inevitable that the oleochemical industries has been flourishing and blooming in the last few years. The majority fatty acid found in palm kernel stearin is C12 which can be found in range of 54.8 to 64.0 wt%. But this value is determined by the iodine and saponification value of the palm kernel. The higher the iodine and saponification value, hence the higher the fatty acid composition can be found for higher extraction for oleochemical plant. The iodine value (Wjis) is ranged from 5.8 to 8.1 whereas the saponification value is ranged from 245 to 254 mgKOHg-1oil. Fuzzy Logic system is developed to determine the fatty acid composition for the different range of iodine value and saponification value to ensure kernel with different composition of fatty acid to be separated and produce higher purity of oleochemical substances. This system will ensure ‘SMART’ manufacturing replacing the ‘NON-SMART’ methods where all kernels are grinded randomly and extracting altogether.